The Effect Of Aerobic Biofilter Method WWTP System On Phosphate In Kediri District Hospital Year 2020 - Harry, Hari Samadyo; Ardi Bastian; Setyo Budi Susanto (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
Laundry activities at the Kediri District Hospital are the largest producer of pollutants in the form of phosphate in the waters in addition to other pollutants if they are not processed first. From some of the data from the analysis of the effluent wastewater quality test in April to October 2020, namely 1,853, 1.8448, 1,490, 2,836, 1,202, 1,340, 1,966 which have a standard value of 2 mg/L (East Java Governor Regulation No. .72 of 2013). This shows that the phosphate parameter in the wastewater effluent has a tendency to increase. Other data show the presence of all indicator fish that died gradually in July 2020 suspected of high phosphate levels. Specific objectives of the research: a. To determine the phosphate content of wastewater before going through the WWTP system with aerobic biofilter method, b. To determine the phosphate content of wastewater after going through the WWTP system with aerobic biofilter method, c. To determine the effect and effectiveness of the WWTP system, the aerobic biofilter method in reducing phosphate levels. The design of this research is quantitative using analytic observational research with cross sectional approach. The sample in this study is part of the hospital wastewater taken from the WWTP. The research data were tested using the Paired Sample T test, pre-test and post-test data. The results showed that from point 1(T1) to point 2 (T2) phosphate levels increased by 8.46%. At point 2 (T2) to point 3 (T3) phosphate levels decreased by 17.43%, at point 3 (T3) to point 4 (T4) phosphate levels decreased by 40%. The results of statistical tests showed that there was no significant reduction effect after going through the WWTP system with the aerobic biofilter method or in any process of the WWTP system at T2, T3, T4. The level of effectiveness of the WWTP system with the aerobic biofilter method of 46.27% is considered to have not been able to give a significant effect. Applicative suggestions include: a. It is necessary to calculate the discharge adjusted to the volume of the bioreactor. b. It is necessary to clean the mud at the bottom of the reservoir regularly and periodically. c. It is necessary to add a tool for aeration in the holding pond. d. It is necessary to measure daily DO, to get the optimal oxygen value, which is 2-4 mg/l. e. It is necessary to review the probiotics that have been used for a long time. f. It is necessary to add an aerator in the final treatment. g. Another way that is more effective and economical is precipitation with the addition of a commonly used coagulant, namely lime. This deposition method can reduce up to 80% of phosphate levels in water, as has been done in previous studies.